An Analysis of Interpersonal Meanings in Students’ Instagram Caption - Fauziyah, Hena Rifa; Nurjannah, Nunung (Universitas Swadaya Gunung Jati, 2019)
Sometimes the writer?s intent (speech function) do not match with mood, it can be happen because they exchange their message through indirect illocutionary act. This exchange meaning phenomenon could be seen in Social Media, such as Instagram. In Instargram, the user write their message or feeling through Caption. This research want to know how the interpersonal meanings are realized when the writer exchange their message through indirect illocutionary act in students? instagram caption. The writer analyzes 17 captions Instagram caption from students in the same University. In this research, the analyzes are based on the theory of Functional Grammar and Speech Function proposed by Halliday (1994) and supported with Illocutionary Acts theory proposed by Searle (1979) and Yule (1996). The method that used in this research is descriptive qualitative method. This reseach show that based on the roles of Illocutionary acts, giving directive like command, recommand, and request and also giving expressive like lament and congratulate can be identified as Indirect Illocutionary Acts in Declarative Mood.